Let p and q be the zeroes of the polynomial f ( x ) = x 2 − 5 x + 4 . Find ∣ ∣ ∣ ∣ p 1 + q 1 − 2 p q ∣ ∣ ∣ ∣ .
Notation: ∣ ⋅ ∣ denotes the absolute value function
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
x 2 − 5 x + 4 = 0
Factor.
( x − 1 ) ( x − 4 ) = 0
x − 1 = 0 or x − 4 = 0
x = 1 or x = 4
So, ∣ ∣ ∣ ∣ p 1 + q 1 − 2 p q ∣ ∣ ∣ ∣ = ∣ ∣ ∣ ∣ 1 1 + 4 1 − 2 ( 1 ) ( 4 ) ∣ ∣ ∣ ∣ = ∣ − 6 . 7 5 ∣ = 6 . 7 5
p = 1 , q = 4 , ∣ p 1 + q 1 − 2 p q ∣ = ∣ 1 + 4 1 − 8 ∣ = 6 . 7 5 .
It was not a clever way, you can do it better with out finding the zeroes and using vieta's formula instead
Log in to reply
For this problem, it suffices to use the roots directly.
As it has the obvious roots, you should use substitution rather then use vieta's formula
You should set a problem without real roots or use a higher degree polynomial, then the use of Vieta's formula will be much convenient.
Problem Loading...
Note Loading...
Set Loading...
We can solve this problem without solving for x .
By Vieta's formula , we have { p + q = 5 p q = 4 . And ∣ ∣ ∣ ∣ p 1 + q 1 − 2 p q ∣ ∣ ∣ ∣ = ∣ ∣ ∣ ∣ p q p + q − 2 p q ∣ ∣ ∣ ∣ = ∣ ∣ ∣ ∣ 4 5 − 2 ( 4 ) ∣ ∣ ∣ ∣ = ∣ − 6 . 7 5 ∣ = 6 . 7 5 .